1987
DOI: 10.5650/jos1956.36.561
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of Microporous Hydrophobic Membrane Bioreactor with respect to Continuous Glycerolysis of Fat by Lipase

Abstract: An attempt was made to scale up the microporous hydrophobic membrane bioreactor with special regard to the lipase-catalyzed glycerolysis of fat. The continuous glycerolysis of olive oil was carried out using Pseudomonas fluorescens lipase with single and multiple piled-up units of the flat micron porous polypropylene membrane Bioreactor developed by the authors. Membrane area ranged from 0.0726 m2 to 1.16 m2 (16-fold scale-up). Two operational modes of the multiple piled-up units, i.e., parallel flow and serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Results obtained clearly showed that the oil flow rate per sheet was the determining factor affecting the concentration of partial acylglycerols regardless of the total surface area of the membrane and the operation protocols namely parallel flow and series flow modes. A DAG yield of∼51 % was reported at an operating temperature of 40°C and a low oil flow rate (0.17-0.27 g h −1 ) per one membrane sheet in both parallel and series flow modes (Koizumi et al 1987). Theoretically, MR system is an acceptable setup.…”
Section: Membrane Reactormentioning
confidence: 97%
See 1 more Smart Citation
“…Results obtained clearly showed that the oil flow rate per sheet was the determining factor affecting the concentration of partial acylglycerols regardless of the total surface area of the membrane and the operation protocols namely parallel flow and series flow modes. A DAG yield of∼51 % was reported at an operating temperature of 40°C and a low oil flow rate (0.17-0.27 g h −1 ) per one membrane sheet in both parallel and series flow modes (Koizumi et al 1987). Theoretically, MR system is an acceptable setup.…”
Section: Membrane Reactormentioning
confidence: 97%
“…Approximately equimolar concentrations of MAG and DAG were synthesized with an insignificant amount of TAG formed (Mozammel Hoo et al 1984). In another work, Koizumi et al (1987) presented and scaled up the microporous hydrophobic MR for lipase-catalyzed glycerolysis reaction. The membrane employed is of polypropylene type with a total surface area ranging from 0.0726 to 1.16 m 2 .…”
Section: Membrane Reactormentioning
confidence: 98%